Contractual incompleteness, limited liability and asset price bubbles - Dow, James; Han, Jungsuk (Journal of Financial Economics, 2015)
When should we expect bubbles? Can levered intermediaries bid up risky asset prices through asset substitution? We study an economy with financial intermediaries that issue debt and equity to buy risky assets. Asset substitution alone cannot cause bubbles because it is priced into the intermediaries׳ securities. But incomplete contracts and managerial agency problems can make intermediaries take excessive risk to exploit limited liability, bidding up risky asset prices. This destroys welfare through misallocation of resources. We argue that incentives for private monitoring cannot solve this problem. Finally, even without agency problems, debt subsidies will create similar effects.